2011
DOI: 10.1074/jbc.c110.181347
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A (CyPA) Induces Chemotaxis Independent of Its Peptidylprolyl Cis-Trans Isomerase Activity

Abstract: Cyclophilin A (CyPA) is a ubiquitously distributed peptidylprolyl cis-trans isomerase (PPIase) that possesses diverse biological functions. Extracellular CyPA is a potent chemokine, which can directly induce leukocyte chemotaxis and contribute to the pathogenesis of inflammation-mediated diseases. Although it has been identified that the chemotaxis activity of CyPA is mediated through its cell surface signaling receptor CD147, the role of CyPA PPIase activity in this process is disputable, and the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 39 publications
5
54
0
1
Order By: Relevance
“…CD147 has been shown to function as a signaling receptor for extracellular Cyps A and B and to mediate the chemotactic activity of Cyp toward a variety of immune cells [26,39] Recent in vitro and in vivo studies have demonstrated a role of Cyp-CD147 interactions in the regulation of inflammatory responses in a number of diseases, including acute lung inflammation, rheumatoid arthritis, and cardiovascular disease [30]. While the interaction of CypA with CD147 has been well characterized by NMR, only a few papers have reported the interaction of CypB with CD147 in immune cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…CD147 has been shown to function as a signaling receptor for extracellular Cyps A and B and to mediate the chemotactic activity of Cyp toward a variety of immune cells [26,39] Recent in vitro and in vivo studies have demonstrated a role of Cyp-CD147 interactions in the regulation of inflammatory responses in a number of diseases, including acute lung inflammation, rheumatoid arthritis, and cardiovascular disease [30]. While the interaction of CypA with CD147 has been well characterized by NMR, only a few papers have reported the interaction of CypB with CD147 in immune cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Defective stress adaptation of the B. abortus ⌬cypAB mutant is dependent on the PPIase activity. It has been reported that functions assigned to cyclophilins do not always depend on its PPIase activity (44,48,49). To determine if the PPIase activity of B. abortus CypB is required for its physiological role, the amino acid residues Arg 55 and Phe 60 were replaced by alanine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CyPA exhibits a wide array of pathophysiological properties, including the induction of inflammatory cell chemotaxis [24,25], the proliferation of VSMC [7,12], and the secretion of matrix metalloproteinases [2,4]. A previous study showed that CyPA is abundantly expressed in atherosclerotic plaque [4].…”
Section: Discussionmentioning
confidence: 99%